Ludloff's medial approach for open reduction of congenital dislocation of the hip - Wataru Koizumi; Hideshige Moriya; K. Tsuchiya; Takashi Takeuchi; Makoto Kamegaya; Tohru Akita (1996)
We reviewed 33 patients (35 hips) after open reduction of congenital dislocation of the hip using Ludloff's medial approach. The mean age at the time of operation was 14 months (5 to 29) and at the time of final follow-up 20.1 years (15 to 24) giving a mean duration of follow-up of 19.4 years (14 to 23). We evaluated the radiological results by the Severin classification and the extent of avascular necrosis using the criteria of Kalamchi. At the latest review 16 hips (45.7%) were in Severin groups I or II (acceptable results) and 19 (54.3%) in Severin groups III, IV or V (unacceptable results). There was evidence of avascular necrosis in 15 hips (42.9%). The radiological results began to become worse at about the age of ten years when type-II avascular changes presented. We conclude that Ludloff's medial approach for open reduction is unsatisfactory for the treatment of congenital dislocation since about half of our patients required additional operations.